Sistema de gestión de seguridad y salud ocupacional para la prevención de accidentes laborales en empresas mineras - Cangahuala Sedano, Jorge Aníbal (2022)
Under the great demand of competitiveness in the mining sector, it is necessary to develop occupational health and safety policies for the well-being of workers in the mining unit, this materializes through a sustainable preventive culture, managing to preserve and optimize human resources. This research has the objective of determining that the Occupational Health and Safety Management System prevents occupational accidents within the company Austin Engineering Peru SAC., 135 workers were worked with, representing 100% of the population, it is an experimental investigation , applied, with a descriptive level and a quantitative approach with a correlational scope, it was possible to reduce the number of accidents and incidents, the reduction of the Severity Indices by 92.11% and the Frequency Index by 70:81%. These achievements allow us to conclude that the application of the system is efficient by reducing the accident rate, the Severity and Frequency index, allowing the company to be more competitive in the market of mining companies.